Enhanced Lithium Storage Performance of CuO Nanowires by Coating of Graphene Quantum Dots - Chao, Dongliang (2016)
Graphene quantum dots prove useful in lithium-ion batteries. This work introduces graphene quantum dots for the first time as surface coating material for lithium-ion battery electrodes, exemplified by copper oxide nanowires. The high-rate capability, initial columbic efficiency, and cycle life are improved by the surface coating.